THE ROLE OF THE CUSTOMER'S PROFIT ANALYSIS IN MAKING PRICING DECISIONS - Amal Abdulhussain Kuhait; Anmar Adnan Khudhair Aldulaimi; Haifa Kazem Ibrahim; Hussein Thamer khadim (Scholars Digest Publishing, 2023)
The current research aims to analyze the role and relationship of the customer's profitability in the process of making decisions, especially pricing decisions. The research relied on the analytical applied approach to obtaining the research results. The research has reached several conclusions, the most important of which is that the customer profit analysis provides important information about the categories of customers that must be focused on or reducing the focus on it and the price that can be determined for each category, and the customer's profitability analysis can determine the categories of customers with high costs and low costs and how to dispose of each category to increase the company's profitability.
Keywords: customer's profit analysis, managerial decisions, pricing decision.